Physical experimental study on the stability analysis of granite residual soil slope with boulder and dominant channel - Zhang, Xuesong; Xia, Chutian; Zhang, Lijuan; Hou, Zhenkun (Frontiers in Earth Science, 2026)
IntroductionGranite residual soil exhibits pronounced engineering characteristics such as strong disintegration, high porosity, and structural heterogeneity, often containing compound structures of boulders and dominant seepage channels. This unique configuration leads to progressive instability and failure of slopes under rainfall infiltration.MethodsTo investigate this mechanism, a physical model testing system was established to analyze the stability characteristics and key influencing factors of granite residual soil slopes with boulders and dominant channels under rainfall conditions.ResultsThe results show that the spatial position of boulders significantly regulates the evolution of the seepage field and the failure mode. Boulders located closer to the slope surface cause stronger local seepage deflection, concentrate the seepage path, accelerate shear zone formation, and enlarge the final landslide scale. The number of dominant seepage channels exerts a dual influence by forming rapid infiltration networks while inducing non-uniform soil saturation, resulting in a pronounced hydro-mechanical coupling effect that shortens slope stability time and increases landslide magnitude. In addition, higher soil compaction densifies the pore structure, reduces water migration, delays saturation, and thereby slows the development of instability.DiscussionAlthough both boulders and dominant seepage channels promote slope instability, their mechanisms differ: dominant channels directly enhance internal water migration through preferential flow paths, whereas boulders indirectly induce new seepage pathways by altering the existing seepage field. Overall, this study elucidates the differential roles of boulders, dominant seepage channels, and soil compaction in rainfall-induced slope failure, providing a theoretical foundation for prevention and control.